The influence of pterygium on corneal densitometry evaluated using the Oculus Pentacam system - Zhang, Jing; Zhang, Liyun; Hu, Huiling; Sun, Liangnan; He, Wenling; Zhang, Zhe; Wang, Jiantao; Nie, Danyao; Liu, Xinhua (Frontiers in Medicine, 2023)
Purpose To assess the effect of pterygium on corneal densitometry (CD) values. Methods One hundred and nine patients (155 eyes) with primary pterygium were divided into a severe pterygium group (79 eyes) and a mild-to-moderate pterygium group (76 eyes) according to pterygium severity. Among them, 63 patients had monocular pterygium; and 25 patients (38 eyes) underwent pterygium excision combined with conjunctival autograft follow-up. A Pentacam anterior segment analyzer was used to obtain the CD values and corneal morphological parameters, including central corneal thickness (CCT), flat-axis keratometry (K1), steep-axis keratometry (K2), corneal astigmatism, irregular astigmatism, and spherical aberration. CD was subdivided into four concentric radial regions based on corneal diameter and three layers according to depth. Results CD values at 0–12 mm of the anterior 120 μm layer, 0–10 mm of the center layer and full thickness, and 2–6 mm of the posterior 60 μm layer were significantly higher in eyes affected by pterygium than in the contralateral unaffected eyes (all P < 0.05). CD values were significantly higher in the severe pterygium group than in the mild to moderate pterygium group (all P < 0.05). Corneal astigmatism, irregular astigmatism, K1, K2, CCT, and spherical aberration correlated with CD values in eyes with pterygium (all P < 0.05). CD values at 6–10, 0–12 mm in the anterior 120 μm layer and full thickness, 10–12 and 0–12 mm in the center layer were significantly decreased 1 month after pterygium surgery compared with those before surgery (all P < 0.05). Conclusion Patients with pterygium had increased CD values, particularly in the anterior and central layers. CD values were correlated with pterygium severity grading and corneal parameters. Pterygium surgery partially reduced the CD values.